1995
DOI: 10.1080/00039896.1995.9935959
|View full text |Cite
|
Sign up to set email alerts
|

Asbestos Bodies in Normal Lung of Western Mediterranean Populations with No Occupational Exposure to Inorganic Dust

Abstract: The aim of this study was to determine the following: (a) asbestos body count in lung tissue of different western Mediterranean populations; (b) the association, if any, of urban industrial residence with higher lung tissue asbestos exposure posed for lung cancer in our population. Lung-tissue samples were studied in three groups of subjects from the general population: (1) group A comprised 18 patients from Barcelona's urban industrial area (mean age = 62.2 y, standard deviation [SD] = 13.6); (2) group B comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 30 publications
0
5
2
1
Order By: Relevance
“…In this study, there is no gender predilection or associated type of occupation identified to relate with AB burden. The residential area also affects the AB burden in lung tissue, the level of AB appears to be higher in urban dwellers from some prior reports while the prevalence is similar between the urban and rural area from some reports [4,7,13]. In addition, no significant association between residential area and concentration of AB was observed in this study.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…In this study, there is no gender predilection or associated type of occupation identified to relate with AB burden. The residential area also affects the AB burden in lung tissue, the level of AB appears to be higher in urban dwellers from some prior reports while the prevalence is similar between the urban and rural area from some reports [4,7,13]. In addition, no significant association between residential area and concentration of AB was observed in this study.…”
Section: Discussioncontrasting
confidence: 46%
“…Asbestos fiber can be found from weathering and erosion of asbestos-containing rocks and road surfaces, tears in brake and clutch pads, weathering of asbestos cement walls and roofing, especially during maintenance, repair and removal processes. Previously, studies from several industrial countries have demonstrated that the percentage of the Asbestos Body (AB) identified using the lung tissue digestion method from general autopsy cases varied from 16.4% to 100% [3 -22], with an increased prevalence in the same population over time [4]. In Thailand, Sri-umpai et al [5] identified AB in 33% of autopsy lungs since 1985.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding figures for total AFs were 0.57×10 6 , 1.16×10 6 , 0.26×10 6 , and 24.6×10 6 / gdw. Monsò et al 28 found ABs in nine out of 18 non-occupationally exposed subjects living in Barcelona (range 0 to 430 AB/gdw). Dufresne et al 29 measured ABs and AFs in the lung of residents in Asbestos never occupationaly exposed and dying from diseases not related to asbestos: the average concentrations were 192 AB/gdw and 208×10 6 AF/gdw.…”
Section: Discussionmentioning
confidence: 99%
“…Counting AB in iron-stained tissue sections and counting AB in digested LT samples are the methods that are most frequently applied to assess the AB content of the lungs. Values >1000 AB·g -1 dry LT and 1-2 AB·tissue section -1 are usually considered as indicative of nontrivial (usually occupational) exposure [5,15,[32][33][34]. The corresponding limits may be somewhat higher in areas where exposure to long amphiboles is common, e.g.…”
Section: Lung Tissuementioning
confidence: 99%